Evaluasi Manajemen Keselamatan pada Pusat Data (Studi Kasus Perguruan Tinggi XYZ) - Aniq Noviciatie Ulfah; Wing Wahyu Winarno (UIN Sunan Kalijaga Yogyakarta, 2017)
Data center was developed related to data security as one of the assets of the organization in addressing the data management for operational purposes as secondary storage media and data distribution. Safety management is part of the framework of the data center that should be assessed by the manager to determine whether compliance with the standards so as to minimize the likelihood of the risk of adverse effects on the organization. This prompted the University XYZ to evaluate the safety management to determine the extent of the implementation of safety management in the data center in their environtment. In evaluating the safety management of the data center in the University XYZ is using the standard ISO 22301: 2012. ISO 22301 is a standard that specifically to plan, establish, implement, operate, monitor, review, maintain and improve a documented management system to protect or reduce the possibility of the risk, be on the alert, handle and recover the time of the incident. The sources of data was obtained from 9 respondents who are heads / staff from each division in the data center University XYZ. The data that have been obtained will be used to measure the maturity level of each clause of the ISO 22301: 2012 and as an evaluation tools. The results obtained in this study indicate that the University XYZ has been implementing safety management in the data center with a value for each clause 5, 6, 7, 8, and 9 are sequential ie 2:42, 2:41, 1:21, 1.67, and 1.65.